2021
DOI: 10.1080/03019233.2021.1972740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of impellers on particle mixing behaviour in KR desulphurization process

Abstract: Three types of impellers are developed to improve reagent efficiency in the desulfurization process of hot metal by kanbara reactor stirring method. The movement and dispersion behavior of particles are investigated using the CFD technology. The flow structure, particle volume fraction distribution and mixing time are taken as the characteristics to describe the entrainment ability and mixing ability of the impellers. The results show that the square center impeller (impeller B) improves the flow structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Dong et al [44] suggested a maximum spout height of 5 cm to control the previous problems. Li et al [74] studied the limits on gas flow rate to prevent electrode washing for a given arc length using a 1:7 geometric scale EAF model. They obtained the following relationship for the spout height (Δh) as a function of stirring energy (ε) and height of the liquid (H)…”
Section: Slag Eye and Spout Height Due To Bgimentioning
confidence: 99%
“…Dong et al [44] suggested a maximum spout height of 5 cm to control the previous problems. Li et al [74] studied the limits on gas flow rate to prevent electrode washing for a given arc length using a 1:7 geometric scale EAF model. They obtained the following relationship for the spout height (Δh) as a function of stirring energy (ε) and height of the liquid (H)…”
Section: Slag Eye and Spout Height Due To Bgimentioning
confidence: 99%
“…When the type of desulfurizer and the condition of molten iron are stable, the degree of mixing and dispersion of desulfurizer in molten iron directly affects the desulfurization efficiency [2,3] . For KR desulfurization, the purpose of stirring is to eliminate the concentration difference, so the desulfurization efficiency can be expressed by studying the stirring efficiency of the paddle [4] . In order to obtain blades with higher mixing efficiency, the mixing time of three blades was studied in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers optimized the flow field using physical simulation experiments [10][11][12] and numerical simulations [13][14][15][16] to improve the dispersion of particles. The effect of the impeller rotation speed [4,[17][18][19], impeller rotation direction [20], impeller immersion depth [16], and impeller geometry [21] on the desulphurization efficiency was performed.…”
Section: Introductionmentioning
confidence: 99%